Corruption Around the World : Causes, Consequences, Scope, and Cures - Tanzi, Vito (IMF Working Papers; Working Paper ;, 1998)
Corruption is attracting a lot of attention around the world. The paper surveys and discusses issues related to the causes, consequences, and scope of corruption and possible corrective actions. It emphasizes the costs of corruption in terms of economic growth. It also emphasizes that the fight against corruption may not be cheap and cannot be independent from the reform of the state. If certain reforms are not made, corruption is likely to continue to be a problem regardless of actions directly aimed at curtailing it.